2019
DOI: 10.3390/cancers11081067
|View full text |Cite
|
Sign up to set email alerts
|

EP300 and SIRT1/6 Co-Regulate Lapatinib Sensitivity Via Modulating FOXO3-Acetylation and Activity in Breast Cancer

Abstract: Forkhead Box O3 (FOXO3) is a tumor suppressor whose activity is fine-tuned by post-translational modifications (PTMs). In this study, using the BT474 breast cancer cells and a recently established lapatinib resistant (BT474-LapR) cell line, we observed that higher FOXO3 and acetylated (Ac)-FOXO3 levels correlate with lapatinib sensitivity. Subsequent ectopic expression of EP300 led to an increase in acetylated-FOXO3 in sensitive but not in resistant cells. Drug sensitivity assays revealed that sensitive BT474 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…As a proof-of-concept, we identified genomic aberrations that correlated with our drug-sensitivity predictive signaling features. For instance, through the lapatinib-predictive median expression levels of p-MKK3 and p-MKK6 we identified the known lapatinib sensitivity predictive EP300 CNV (Mahmud et al, 2019) and the interesting PPM1D CNV, which encodes a serine threonine phosphatase amplified in approximately 8% of breast cancers (Lambros et al, 2010). Furthermore, the lapatinib-predictive p38·MK2 edge flux linked amplification of the breast cancer oncogene A1CF (Yan et al, 2017), and of ASAH2B to lapatinib resistance.…”
Section: Discussionmentioning
confidence: 99%
“…As a proof-of-concept, we identified genomic aberrations that correlated with our drug-sensitivity predictive signaling features. For instance, through the lapatinib-predictive median expression levels of p-MKK3 and p-MKK6 we identified the known lapatinib sensitivity predictive EP300 CNV (Mahmud et al, 2019) and the interesting PPM1D CNV, which encodes a serine threonine phosphatase amplified in approximately 8% of breast cancers (Lambros et al, 2010). Furthermore, the lapatinib-predictive p38·MK2 edge flux linked amplification of the breast cancer oncogene A1CF (Yan et al, 2017), and of ASAH2B to lapatinib resistance.…”
Section: Discussionmentioning
confidence: 99%
“…When the FOXO3 is activated, it could induce transcription of target genes through binding to the conversed sequence motif GTAAA(C/T)A [ 21 ]. In breast cancer, Mahmud et al demonstrated that EP300 and SIRT1/6 co-regulates Lapatinib sensitivity through modulating FOXO3-acetylation and activity [ 22 ]. Another study found that lnRNA LINC01355 could stabilize FOXO3 protein and inhibit the progression of BC [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…EP300 encodes the repressor histone acetyltransferase protein p300, which also has roles as a transcriptional corepressor protein. EP300 has been implicated in modulation of FOXO3 activity (Mahmud et al 2019) and in Beta coefficients, p values and 95% confidence intervals (95% CI) are given for associations between circRNA expression and hand grip strength. Three hundred six individuals were assessed.…”
Section: Discussionmentioning
confidence: 99%